What the Paris 1924 olympics tell us about promoting oral health for community sport - a call to action - Ian Needleman (BMC, 2024)
Abstract Sport participation has huge benefits to individuals and communities including both physical health and wellbeing, prevention of non-communicable diseases, promoting equity and reducing inequalities. Sport participation can disadvantage oral health with a life-long shadow of treatment need and potential psycho-social consequences, despite these problems being preventable. It is therefore a priority to collaborate with partners in community sport to embed oral health promotion as one of the foundations of overall health in order to gain the most equitable and sustainable benefits from sport participation.